Cytokine profile in patients with early latent syphilis. - Zakharov, S. V. (Medicni Perspektivi, 2018)
The purpose of this study was to study the change in the content of the most active cytokines (interleukins 6 and 10) during the formation of the immune response in patients with latent early syphilis, as well as to study the possible relationship between the concentrations of these cytokines and the duration of the disease. In 50 patients with early latent syphilis, the concentration of interleukins 6 and 10 in serum was studied. The serum level of interleukins was studied by the enzyme immunoassay. A statistically significant increase in the concentration of interleukin 6 in the blood of patients with latent syphilis and decrease in the interleukin 10 concentration in comparison with healthy people was established. At the same time, in patients with latent syphilis with term of infection for more than 1 year, interleukin 10 has been expressed, as compared with healthy people and, especially, with patients with syphilis with a duration of infection of up to 1 year. Along with this, a lower degree of increase in the concentration of interleukin 6 in patients with latent syphilis with a duration of infection over 1 year has been established, as compared with patients with latent syphilis with a term of infection up to 1 year, against the background of its increased concentration as compared with a group of healthy individuals.